Evaluation of kefir consumption on gut microbial diversity in a healthy young population using full-length 16S rRNA sequencing - Yejin Choi; Gi Beom Keum; Juyoun Kang; Hyunok Doo; Jinok Kwak; Haram Kim; Yeongjae Chae; Suyoung Lee; Hyunjin Yang; Sheena Kim; Xingmin Sun; Hyeun Bum Kim; et al. (Frontiers in Microbiology)
IntroductionA balanced gut microbiota is essential for maintaining digestive, immune, and metabolic health. Kefir, a fermented milk beverage, influences gut microbiota through its probiotic composition and bioactive compounds, exhibiting various health-promoting effects. However, evidence on the effects of kefir on gut microbiota, particularly in healthy populations, is still limited. This study aimed to elucidate the effects of kefir on gut microbiota composition in healthy young adults under a controlled dietary environment.MethodsIn this randomized, controlled, parallel-group trial, 28 healthy participants aged 18–30 years were assigned to one of three groups: kefir (n = 13), unfermented milk (n = 9), and yogurt (n = 6). Participants consumed 150 mL of their assigned beverage daily for 2 weeks. Stool samples were collected before and after the intervention to analyze gut microbiota composition using 16S rRNA sequencing.ResultsKefir consumption increased the relative abundance of lactate-producing bacteria, including Bifidobacterium breve, Ruthenibacterium lactatiformans, Weissella koreensis, and Leuconostoc mesenteroides. The genus Blautia also increased, with significant changes observed in Blautia luti and Blautia wexlerae. These shifts in species abundance were associated with increases in the short-chain fatty acid (SCFA) production pathway.DiscussionIn summary, this study highlights kefir's potential to modulate gut microbiota composition in healthy individuals, emphasizing its role in supporting gut health.